2005
DOI: 10.1093/aje/kwi203
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Prostate Cancer Risk: A Case-Control Study

Abstract: Observational studies have shown that 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor (statin) use may be associated with reduced cancer risk. The purpose of this case-control study was to elucidate the association between statin use and prostate cancer risk. Prostate cancer cases (n ¼ 100), recruited upon referral for prostate biopsy, and frequency age-matched, prostate-specific antigen-normal clinic controls (n ¼ 202) were recruited from the Portland, Oregon, Veterans Affairs Medical Center. Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(115 citation statements)
references
References 20 publications
(47 reference statements)
5
110
0
Order By: Relevance
“…Of note, safety of this class of agents was confirmed by several meta-analyses [14,15]. Notwithstanding, several epidemiological studies have suggested that HMG-CoA reductase inhibitors may, in fact, prevent certain solid malignancies such as melanoma, breast, colon, and prostate cancers [16][17][18][19][20]. Likewise, it has been suggested that chronic statin use is linked with a trend toward a lower cancerrelated mortality rate [21].…”
Section: Epidemiological Evidencementioning
confidence: 89%
“…Of note, safety of this class of agents was confirmed by several meta-analyses [14,15]. Notwithstanding, several epidemiological studies have suggested that HMG-CoA reductase inhibitors may, in fact, prevent certain solid malignancies such as melanoma, breast, colon, and prostate cancers [16][17][18][19][20]. Likewise, it has been suggested that chronic statin use is linked with a trend toward a lower cancerrelated mortality rate [21].…”
Section: Epidemiological Evidencementioning
confidence: 89%
“…However, Cappelli et al [16], in a retrospective study on 137 patients on statins (104 on simvastatin [hydrophobic], 29 on atorvastatin [hydrophilic], 1 on pravastatin, and 1 on rosuvastatin), did not detect a relationship between the number and volume of thyroid nodules and molecule type. While the duration of statin use is reportedly a stronger predictor than the daily dose for a reduction in the risk of developing prostate cancer, Shannon et al [37] concluded that nodules are less prevalent among patients taking a greater mean daily dose, independent of duration.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the different characteristics of the four study settings, an inverse association between longer-term use of statins and prostate cancer was observed in each, with point estimates of 0.26 [19], 0.60 [16], 0.57 [17] and 0.75 [18]. A small case-control study [20] of 100 men with prostate cancer recruited upon referral for biopsy found a 62% reduction in the risk of prostate cancer (OR = 0.38 [0.21-0.69]) with statin use. Lastly, a large population-based study reported by Teemu et al [21] showed no evidence for reduced overall prostate cancer risk among users of cholesterol-lowering drugs, but found a decreased risk of advanced cancer among statin users ( …”
Section: Introductionmentioning
confidence: 92%